Localization of workforce in Saudi Arabia: historical review of the problem - Alwethainani, Mohammed; Mansor, Zuraina (Publications International, 2016)
Recently Saudi government is facing the unemployment challenges due to high number of international labour working in the Saudi Arabia. This caused severe threat to the local workforce. The purpose of this study was to explore the persistence of the current unemployment crisis in Saudi Arabia and alternative strategies that might be designed to reduce unemployment in Saudi Arabia. Localization of the workforce is one of the major initiatives taken by the Saudi government to reduce the unemployment of their local workforce. The research proposes a framework for reducing the number of illegal expatriates. Current study comprehensively reviewed the effectiveness of the measure taken by the Saudi government. Literature indicated that the internalization of the workforce initiatives has significantly reduced the unemployment of the Saudi workforce. However the problem still exists and Saudi government and policy makers still required to develop more effective strategies to cop the situation.